1996
DOI: 10.1007/bf03401644
|View full text |Cite
|
Sign up to set email alerts
|

The Repertoire of CD4+ CD28− T Cells in Rheumatoid Arthritis

Abstract: Oligoclonality is a characteristic feature of CD4+ CD28- T cells which are expanded in some healthy individuals and in the majority of RA patients. The lack of CD28 expression is a common denominator of CD4+, CD8+, and CD4- CD8- T cells prone to develop clonal dominance. The limited TCR diversity of clonal CD4+ CD28- populations in RA patients suggests that these T cells recognize a limited spectrum of antigens. The fact that the majority of individuals with marked expansions and oligoclonality of CD4+ CD28- T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 38 publications
1
87
0
2
Order By: Relevance
“…Studies from various laboratories have consistently demonstrated that these oligoclonal T cells are deficient in expression of the CD28 costimulatory receptor (17,(35)(36)(37). CD4ϩ,CD28 null T cells are long-lived, functionally aberrant lymphocytes (38).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from various laboratories have consistently demonstrated that these oligoclonal T cells are deficient in expression of the CD28 costimulatory receptor (17,(35)(36)(37). CD4ϩ,CD28 null T cells are long-lived, functionally aberrant lymphocytes (38).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that an unusual subset of CD4 ϩ CD28 null T cells is expanded in RA (47,48). These T cells are likely to require costimulatory signals distinct from CD80/CD86.…”
Section: Costimulation In Ramentioning
confidence: 99%
“…Possibly, CD4ϩ,CD28Ϫ T cells recognize alloantigens on FLS lines. However, CD4ϩ,CD28Ϫ T cells are generally oligoclonal (39) and have been shown to be defective in alloreactive responses (40). In contrast, CD4ϩ,CD28Ϫ T cells respond vigorously in autologous mixed-lymphocyte reactions and may indeed be autoreactive (26).…”
Section: Discussionmentioning
confidence: 99%